Political exercise : active living, public policy, and the built environment - Brown, Lawrence D. (New York : Columbia University Press, 2022)
"The public health benefits of giving city dwellers increased opportunities to lead physically active lifestyles are well known to urban planners, public health scholars, and government officials. Moreover, increases in "active living," such as walking and cycling, help the environment, support local businesses, and reduce traffic congestion, among other advantages. But despite wide agreement that active living is both achievable and valuable, best practices are not easy to implement. In Political Exercise, Lawrence D. Brown presents five case studies of cities that have promoted active living with varying success through a range of approaches. He shows how and why the transformation of a call for public intervention into projects, programs, and policies is inescapably political. Brown argues that in order to implement policies that support active living, their proponents must give communities a sense of ownership of recommended changes in the built environment, filter the public health agenda through a range of public and private organizations, and secure committed political champions. At the intersection of public health and urban planning, Political Exercise offers a framework for scholars, policy makers, and reformers to more productively address both the rationales behind active living and the political strategies that spur change"--
Intro -- Table of Contents -- Acknowledgments -- Introduction -- 1. Wilkes-Barre: Active Living on the Trail to Recovery -- 2. Louisville: The Politics of Piecemeal Progress -- 3. Albuquerque: Reshaping a Cultural Landscape -- 4. Sacramento: Active Living as a Breath of Fresh Air -- 5. New York City: Flourishing at the Margins of Policy -- 6. Evaluation Meets Implementation: The Struggle for the Real -- Conclusion: Active Living and Beyond: Bringing Implementation Back Into Health Promotion -- Notes -- References -- Index
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on April 05, 2022).
Keywords: Public health -- Political aspects -- Case studies; Public health -- Social aspects; Health planning; City planning -- Health aspects; Health Planning; Santé publique -- Aspect politique -- Études de cas; Sociologie de la santé.; Santé publique -- Planification; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development; City planning -- Health aspects; Health planning; Public health -- Political aspects; Public health -- Social aspects; Electronic books; Case studies